The role of extracellular vesicles in biomineralisation: current perspective and application in regenerative medicine - Azoidis, Ioannis (J Tissue Eng, 2018)
Extracellular vesicles comprise a heterogenous population of exosomes and microvesicles that have critical roles in intercellular signalling and tissue development. These complex particles have been implicated as mediators of the therapeutic effects of stem cells via the transfer of an assorted cargo of proteins and nucleic acids, which can modulate inflammation and enhance endogenous regeneration in a range of tissues. In addition, extracellular vesicles have the capacity to be loaded with therapeutic molecules for targeted delivery of pharmaceuticals. The versatility, biostability and biocompatibility of extracellular vesicles make them appealing for regenerative medicine and may endow considerable advantages over single molecule approaches. Furthermore, since production can be optimised and assessed ex vivo, extracellular vesicles present a decreased risk of neoplastic transformation when compared with cell-based methods. To date, the contribution of vesicles to tissue development has perhaps been most comprehensively defined within hard tissues, such as endochondral bone, where they were first identified in 1969 and henceforth referred to as matrix vesicles. Within developing bone, vesicles function as vehicles for the delivery of pro-osteogenic factors and initiate early nucleational events necessary for matrix mineralisation. However, advancement in our understanding of the biogenesis and characterisation of matrix vesicles has occurred largely in parallel to associated developments in wider extracellular vesicle biology. As such, there is a requirement to align current understanding of matrix vesicle–mediated mineralisation within the context of an evolving literature surrounding exosomes and microvesicles. In this review, we present an overview of current progress and opinion surrounding the application of vesicles in regenerative medicine with a primary focus on their potential as an acellular approach for enhancing hard tissue regeneration. This is balanced with an assessment of areas where further development is required to maximise their application for regenerative medicine.